2009
DOI: 10.1210/er.2009-0001
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast Stem Cells: Models for Investigating Trophectoderm Differentiation and Placental Development

Abstract: The placenta is an ephemeral organ containing diverse populations of trophoblasts that are all derived from the embryonic trophectoderm but have morphological, functional, and molecular diversity within and across species. In hemochorial placentation, these cells play especially important roles, interfacing with and modifying the cells of the maternal decidua. Within the rapidly growing placenta, it has been shown that there are trophoblast stem cells well character-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 105 publications
4
45
1
Order By: Relevance
“…As discussed earlier, the idea that BMP4 can drive hESCs to trophoblast has been controversial (31), despite evidence that both mouse ESCs and hESCs have the potential to differentiate along extraembryonic lineages under appropriate culture conditions (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Moreover, recent evidence suggests that BMP signaling has a role in ensuring the correct development of the trophoblast lineage in preimplantation mouse embryos (59,60) and that, by the 16-cell morula stage, only the outer cells are fully equipped to respond to signals initiated by BMP4 and related ligands, such as BMP7 (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed earlier, the idea that BMP4 can drive hESCs to trophoblast has been controversial (31), despite evidence that both mouse ESCs and hESCs have the potential to differentiate along extraembryonic lineages under appropriate culture conditions (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Moreover, recent evidence suggests that BMP signaling has a role in ensuring the correct development of the trophoblast lineage in preimplantation mouse embryos (59,60) and that, by the 16-cell morula stage, only the outer cells are fully equipped to respond to signals initiated by BMP4 and related ligands, such as BMP7 (59).…”
Section: Discussionmentioning
confidence: 99%
“…hESCs and iPSCs will also differentiate to the extraembryonic trophoblast lineage either when they are allowed to form embryoid bodies (12,13) or when BMP4, or certain of its homologs, including BMP2, BMP5, BMP7, BMP10, and BMP13, are present in the medium and FGF2 is absent (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The BMPdriven process is accelerated and directionality is enhanced if the signaling pathways that maintain the pluripotent state are inhibited (25).…”
mentioning
confidence: 99%
“…Fundamental insights into the molecular control of trophectoderm determination and differentiation have been made in the past decade Douglas et al, 2009;Ralston and Rossant, 2005). A number of transcription factors and signaling pathways have been identified as crucial players.…”
Section: Trophoblast Stem Cellsmentioning
confidence: 99%
“…This differentiation occurred without extensive generation of mesoderm, endoderm, and ectoderm derivatives, as judged by microarray analysis of transcribed genes, although a low level of expression of genes characteristic of mesoderm and endoderm did occur. This model has become widely used (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) to study an aspect of early human development that is not easily addressed otherwise because of lack of access to human embryos. Over the course of these studies it was demonstrated that the key to obtaining differentiation primarily to TR rather than to other lineages when using BMP4 as the triggering agent was to exclude FGF2, a factor required for maintenance of hESC (14)(15)(16)(17).…”
mentioning
confidence: 99%